1996
DOI: 10.1007/s004240050291
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the relative expression of cardiac and skeletal alpha1 subunit isoforms of L-type calcium channel during in vitro myogenesis

Abstract: Cardiac and skeletal type of excitation-contraction coupling (ECC) are quite different. Those differences could be explained by structural ones in the molecular entities involved in ECC, ie dihydropyridines (DHP) receptors (alpha1 subunit of L-type calcium channels) of the sarcolemma or ryanodine receptors of the sarcoplasmic reticulum membrane. As previously demonstrated by means of electrophysiology, the two types of ECC coexist during the first stages of in vitro development of skeletal muscle, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Differentiation of H9c2 cells to myotubes resulted in the expression of both subunits on the transcriptional level. This is in line with a study on subunit expression in primary skeletal muscle cell cultures from hindlimbs of neonatal rats [Bulteau et al, 1997] demonstrating co-expression of both subunits in earlier states of myotube formation during in vitro myogenesis. Reduced transcript levels for phospholamban and the cardiac ryanodine receptor and diminished protein expression of the cardiac subunit of the L-type Ca 2ϩ channel furthermore characterize the skeletal muscle-like phenotype of H9c2 myotubes.…”
Section: Discussionsupporting
confidence: 84%
“…Differentiation of H9c2 cells to myotubes resulted in the expression of both subunits on the transcriptional level. This is in line with a study on subunit expression in primary skeletal muscle cell cultures from hindlimbs of neonatal rats [Bulteau et al, 1997] demonstrating co-expression of both subunits in earlier states of myotube formation during in vitro myogenesis. Reduced transcript levels for phospholamban and the cardiac ryanodine receptor and diminished protein expression of the cardiac subunit of the L-type Ca 2ϩ channel furthermore characterize the skeletal muscle-like phenotype of H9c2 myotubes.…”
Section: Discussionsupporting
confidence: 84%
“…In this respect, it is important to note that newborn cardiac myocytes in primary culture express functional ␣ 1S that generates contractile activity (42). Conversely, skeletal muscle cells in vitro, as well as developing muscle cells in vivo, do express cardiac ␣ 1C mRNA (43,44). Altogether, our data provide new insights into the tissue-specific expression of L-type Ca 2ϩ channel isotypes and further suggest that the expression of functional skeletal L-type Ca 2ϩ channels can occur within the cardiac cell lineage through a de-differentiation process demonstrated in vitro in a cardiac cell line model.…”
Section: Retinoic Acid Modulation Of Ca 2ϩ Channel Expressionmentioning
confidence: 71%
“…Chaudhari and Beam (1993) showed that mRNA for the cardiac ␣ 1C subunit is abundant in dysgenic and normal muscle. Furthermore, mRNA for ␣ 1C has been reported in a dysgenic cell line (Varadi et al, 1995), as well as in primary cultures of normal myotubes (Bulteau et al, 1977) and in normal adult rodent skeletal muscle (Pereon et al, 1997). Cardiac-type Ca 2ϩ currents are also present in the dysgenic cell line (Varadi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%